Effects of different water and fertilizer concentration on leaf area and yield of jujube (ziziphus jujuba mill.) (Bangladesh Journal of Botany, 2024)
Effects of different water and fertilizer concentrations on the leaf area index, fruit development and yield of jujube trees under bubbled-root irrigation during the growth period were analyzed. The leaf area index of different water and fertilizer treatments reached a peak at the fruit enlargement stage of the jujube tree. The leaf area index reached maximum with high water and medium fertilizer treatment (W1N2).  The highest number of fruits per unit branch length appeared in medium water and medium fertilizer treatment (W2N2), while the lowest appeared in low water treatment (W3N0). The highest yield of all treatments was with medium water and medium fertilizer treatment (W2N2) having a yield of more than 30 000 kg/hm2, while the lowest was with low water and high fertilizer treatment  (W3N1) having a yield of less than 15 000 kg/hm2. Therefore, medium water and medium fertilizer treatment can be selected to obtain the highest yield of jujube trees.Bangladesh J. Bot. 53(4): 881-887, 2024 (December)